In vitro periodontal ligament cell expansion by co-culture method and formation of multi-layered periodontal ligament-derived cell sheets - Ihab Nabeel Safi (Regenerative Therapy, 2019)
Objective: Per-implantitis is one of the implant treatment complications. Dentists have failed to restore damaged periodontium by using conventional therapies. Tissue engineering (stem cells, scaffold and growth factors) aims to reconstruct natural tissues. The paper aimed to isolate both periodontal ligament stem cells (PDLSCs) and bone marrow mesenchymal stem cells (BMMSCs) and use them in a co-culture method to create three-layered cell sheets for reconstructing natural periodontal ligament (PDL) tissue. Materials and methods: BMMSCs were isolated from rabbit tibia and femur, and PDLSC culture was established from the lower right incisor. The cells were co-cultured to induce BMMSC differentiation into PDL cells. Cell morphology, stem cells and PDL-specific markers (CD90, CD34, and periostin) were also detected using immunofluorescent assay. Co-cultured cell monolayers were detached using temperature-responsive tissue culture dishes and collagen graft to create the three-layer construct. The 3D-engineered tissue was examined histologically and by field emission scanning electron microscopy (FESEM). Results: BMMSCs co-cultured with PDLSCs successfully induced more PDL cells. The newly induced PDL cells exhibited periostin and CD90 expression. Fluorescence green intensity was measured for the co-cultured cells that were stained with periostin, the mean fluorescence green intensity (periostin expression) was significantly higher for the newly induced PDL cells after 1, 2, and 3 weeks when compared with control (BM-MSCs), at 21 days non-significant difference was measured when compared with control (PDLSCs).The results showed the successful formation of 3D multilayer PDL tissue. Histological cross-section showed cell sheets and the stable adhesion between them. FESEM examination was conducted for the cross-section, showing three-layered cell sheets with stable adhesion between cells. Conclusions: The results of this paper report that the three layered-cell sheets were successfully constructed by the novel use of collagen graft as a scaffold to be used in treatment of periodontitis and to envelop the dental implants to create biohybrid implant. Keywords: Collagen graft, Mesenchymal stem cells, Periostin, Isolation PDL, Scaffold, Three-dimension culture